Optimalisasi Program Pekarangan Pangan Lestari (P2l) Dalam Upaya Pemenuhan Kebutuhan Masyarakat di Desa Lompulle Kecamatan Ganra Kabupaten Soppeng - Haslinda,; St Aisyah,; Ilham Syah, (Jurnal Berita Sosial, 2023)
This type of research is classified as qualitative with the approach used is the empowerment approach. The data sources of this research are officers of the food crops, horticulture, plantation and food security offices of Soppeng Regency, agricultural extension workers, village heads and members of KWT Lompulle Village. The data collection methods are observation, interview and documentation. Then, data processing and data analysis techniques were carried out through three stages, namely: data reduction, data presentation and conclusion drawing. The results of this study indicate that the form of implementation of the Sustainable Food Yard (P2L) program in Lompulle Village consists of: a) optimizing the role of farm women groups, b) mentoring farm women groups and c) plant breeding. The results of the implementation of the sustainable food yard program in Lompulle Village consist of: a) meeting some of the needs of the community, b) saving household costs, c) utilizing vacant land, d) increasing the community's planting ethos and e) empowering housewives. The implications of this research are: 1) From the Office of Food Crops, Horticulture, Plantations and Food Security of Soppeng Regency to pay more attention to every development of the program and support the implementation of the program by providing assistance to P2L beneficiaries so that the results obtained are optimal and KWT mothers to continue to maintain and maintain plants by continuing to innovate so that they become real examples to the community which can foster community interest in being actively involved in the P2L program, 2). It is hoped that the community will have a place / container that can become a center for selling plant production so that excess crops can be of selling value so that the implementation of the Sustainable Food Yard (P2L) program can also be a source of additional income to increase community income.